Edukasi dan Pendamping Hukum Waris bagi Masyarakat Karang Indah Kelurahan Sumur Dewa Kota Bengkulu - Fahimah, Iim; Bunga, Bunga; Ariska, Anis; Bintang, Satria Alfattah; Apriansyah, M; Utami, Raty Tri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service project was carried out by students of KKN MBKM Group 1, Batch IV 2025, from Fatmawati Sukarno State Islamic University of Bengkulu. The focus was on protecting the inheritance rights of parents and the elderly as a means to promote social justice in the community. The aim of this activity was to evaluate the effectiveness of legal education and assistance in improving public understanding of inheritance rights for parents and elderly individuals, while also preventing inheritance disputes among family members in RT 19 Karang Indah, Sumur Dewa Village, Bengkulu City. The method used was a participatory approach involving legal counseling sessions, group discussions, and direct consultations with residents and community leaders. The results showed that most people lacked adequate knowledge of inheritance law, both in Islamic and civil legal systems. However, after receiving the education, there was a notable increase in legal awareness and active participation in ensuring the inheritance rights of parents and the elderly were respected. This initiative also strengthened intergenerational relationships and received a highly positive response from the community.